ANALISA HASIL UJI KOMPRESOR SISTEM REFRIGERASI MENGGUNAKAN INVERTER - Nuraeni Suryaman, Nia; Riyandi Noordianto, Eki (Universitas Majalengka, 2023)
One of the largest uses of electrical energy is electrical energy used in air conditioning. Electrical power consumption for air conditioning has a figure of about 50-60% of the total electrical energy consumption of a building. In the industrial world, air conditioning or refrigeration systems are used to maintain the temperature conditions of raw materials or products produced with the intention of extending storage life through the cooling process. Refrigeration systems use compressor motors as a medium to circulate refrigerant throughout the system. This study aims to compare three parameters in a refrigeration system that uses an inverter on its compressor motor compared to a conventional refrigeration system. The three parameters are electrical power, cooling capacity and COP (Coefficient of performance). The research was conducted using an analysis-based method of existing systems. Data collection was carried out twice in steady conditions. The results of this study obtained the following data: The use of inverters in refrigeration compressors decreased electrical power by 18.3% increased COP in refrigeration systems by 44.1% and increased cooling capacity by 31.2%.